2009
DOI: 10.2174/092986709788186075
|View full text |Cite
|
Sign up to set email alerts
|

Pertinence of Apoptosis Markers for the Improvement of In Vitro Fertilization (IVF)

Abstract: In assisted reproductive technology (ART), the pregnancy and birth rates following in vitro fertilization (IVF) attempts are still low. Recently, apoptotic markers have been suggested as new criteria for oocyte and embryo quality selection. Many studies have provided evidence that poor oocyte and embryo quality can be associated with apoptosis. The aim of this review is to summarize our current knowledge on the apoptotic process in oocytes and embryos, and focus on the possibility for using apoptotic markers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 130 publications
(161 reference statements)
1
26
1
1
Order By: Relevance
“…It is expected that CCs show signs of apoptosis at the final maturation stage. Some authors have even suggested to use these apoptotic genes during folliculogenesis as potential markers of oocyte development potential [52]. Surprisingly and in parallel to these apoptotic events, the expression of some cell death genes in CCs was markedly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that CCs show signs of apoptosis at the final maturation stage. Some authors have even suggested to use these apoptotic genes during folliculogenesis as potential markers of oocyte development potential [52]. Surprisingly and in parallel to these apoptotic events, the expression of some cell death genes in CCs was markedly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…During postnatal life, the oocyte stockpile continues to be depleted until exhaustion at the moment of menopause (for reviews, see and Haouzi & Hamamah (2009)). Moreover, if the few ovulated oocytes (300-400 during a woman's reproductive life) are not fertilized on time, they will succumb to apoptotic death .…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis occurs frequently early embryonic development and has a significant impact on the development of the embryo [39]. Therefore, we investigated the expression patterns of three apoptosis-related genes, Bcl-xl, Bak and Caspase-3.…”
Section: Discussionmentioning
confidence: 99%